Increase in breath hydrogen concentration was correlated with the main pancreatic duct stenosis. (12th March 2018) - Sakai, Daisuke; Hirooka, Yoshiki; Kawashima, Hiroki; Ohno, Eizaburo; Ishikawa, Takuya; Suhara, Hiroki; Takeyama, Tomoaki; Koya, Toshinari; Tanaka, Hiroyuki; Iida, Tadashi; Nishio, Ryo; Suzuki, Hirotaka; et al.
Abstract: Background. Hydrogen is produced from unabsorbed carbohydrates in the intestine through degradation and metabolism by hydrogenase of intestinal bacteria. The hydrogen is then partially diffused into blood flow and released and detected in exhaled breath. Pancreatic juice production is decreased in patients with reduced pancreatic exocrine function, including those with pancreatic cancer, thus decreasing digestion and absorption of nutrients including carbohydrates, which may increase undigested carbohydrates in the intestine and increase breath hydrogen concentration (BHC). The aim of this study was to investigate the association between BHC and pancreatic diseases. Methods. A retrospective study was designed and 68 patients underwent morning fasting breath hydrogen test. Since there is no clear standard, normal BHC, the median of the measured values from the subjects (9 ppm) was adopted as the standard. The subjects were classified into those with a value exceeding the median (BHC high group: 32 patients) and a value equal to or below the median (BHC low group: 36 patients). Patients characteristics, blood test results and imaging findings characteristic of pancreatic diseases were compared between the groups. Results. The age was significantly higher ( P = 0.010) and the incidences of pancreatic ductal adenocarcinoma and autoimmune pancreatitis were significantly higher ( P = 0.018 and P = 0.004, respectively) in the BHC high group. With respect to the blood test items, the Alb level was significantly lower in the BHC high group ( P = 0.005). With respect to the characteristic imaging findings of pancreatic diseases, the proportions of patients with pancreatic enlargement, the main pancreatic duct (MPD) stenosis, and the MPD dilatation were significantly higher in the BHC high group ( P = 0.022, P < 0.001, and P = 0.002, respectively). On univariate analysis, only the MPD stenosis was extracted as an independent factor ( P = 0.014). Conclusion. It was suggested that the fasting BHC is associated with pancreatic diseases causing stenosis of the MPD, including pancreatic cancer (UMIN000020777).